Management and Perinatal Outcome In Patients With Systemic Lupus Erythematosus - Araneda A. Poblete , José A. Carvajal (Academic Journal of Clinicians, 2024)
The prenatal control and maternal-perinatal outcome of a group of patients with Systemic Lupus Erythematosus who controlled their pregnancy and resolved their delivery during a period of one year in the maternity ward of the Clinical Hospital of the Pontificia Universidad Católica de Chile are presented. We also show a brief critical review of the literature regarding this association. We show that an adequate prenatal diagnosis of the disease, together with strict multidisciplinary control of this pathology during pregnancy, allows reducing maternal and perinatal risks.